Answer:
30 beads to be exact your welcome
Step-by-step explanation:
Answer:
809-8-90-24+5
Step-by-step explanation:
Find the value of f(2).
y = f(x)
y
10
8
6
4
15
2
-10
-8
-6
-4
-2
2
4
6
Answer:
<h3>A B C D E F G H I J K L M N O P Q R S T U V W X Y Z</h3>
For the top question, the answer is D
Because 16 divide by 4, equals 4
Answer:
g(x) = - sqrt(x+8) reflected about the x axis and shifted 8 units to the left
h(x) = 2 sqrt(x) +1 is stretched by 2 in the y direction and shifted up 1 in the y direction
Step-by-step explanation:
y = f(x + C) C > 0 moves it left
So we moved it 8 units to the left
y = −f(x) Reflects it about x-axis
g(x) = - sqrt(x+8) reflected about the x axis and shifted 8 units to the left
y = f(x) + C C > 0 moves it up
so we moved it up 1 units
y = Cf(x) C > 1 stretches it in the y-direction
and stretched it by 2 in the y direction
h(x) = 2 sqrt(x) +1 is stretched by 2 in the y direction and shifted up 1 in the y direction